Nāṭaka mūvar : karuttaraṅku (Tamiḻttuṟai, Pāttimāk Kallūri, 1978)
Symposium on the dramatic style of three veteran dramatists, Sankaradas Swami, 1867-1922, V.G. Suryanarayana Sastriar, 1870-1903, and Pammal Sambanda Mudaliar, 1873-1964 and their contribution to the development of Tamil drama; organized by the Dept. of Tamil, Fatima College, Madurai.